Micro‐Level Discursive Strategies for Constructing Shared Views around Strategic Issues in Team Meetings - Kwon, Winston; Clarke, Ian; Wodak, Ruth (Journal of Management Studies, 2014)
Abstract Management scholars have explored how certain actors in meetings – especially leaders – shape social processes of interaction and use different linguistic devices, as methods, to affect how sense is made of strategic issues. Less attention has been paid to interactions between members of the team as a whole and the repertoire of discursive strategies, or goal‐directed behaviours, that they deploy to create shared views around issues. We analyse rare empirical episodes of team discussions of strategic issues in board meetings to inductively conceptualize how this is achieved. To do this we use theDiscourse‐HistoricalApproach (DHA) to critical discourse analysis (CDA). We reveal five discursive strategies teams use to develop shared views around strategic issues (Re/defining,Equalizing,Simplifying,Legitimating, andReconciling) and demonstrate how they are skilfully operationalized through a range of linguistic devices or means.